Histopathology of Nephrectomy Specimens in a Tertiary Care Hospital, India: A Review - Bharti Devi Thaker; Kailash Singh (New Horizons in Medicine and Medical Research Vol. 1, 2022)
This study was undertaken retrospectively in the Department of Pathology, GMC Jammu, over a two-year period to determine the Histopathological spectrum of illnesses observed in these obtained nephrectomy specimens and compare it to other studies. 70 nephrectomy specimens were obtained in total. Males accounted for 40 (57%) of the cases, while females accounted for 30 (43 %). The cases ranged in age from 3 to 70 years old. The age range 41-50 years had the highest percentage of patients. Non-neoplastic tumours were the most common (62 instances), followed by malignant tumours, and benign tumours were the least common. The most prevalent inflammatory illness for which nephrectomy was performed was chronic pyelonephritis (30 instances). The most common malignant tumour was clear cell renal carcinoma, which had three occurrences. The most prevalent clinical complaint was pain in the flanks. There were more non-neoplastic lesions than neoplastic ones. The most common histological diagnosis was chronic pyelonephritis. Among the malignant tumours, renal cell carcinoma was the most common.